European Code against Cancer 4th Edition: Diet and cancer. (December 2015) - Norat, Teresa; Scoccianti, Chiara; Boutron-Ruault, Marie-Christine; Anderson, Annie; Berrino, Franco; Cecchini, Michele; Espina, Carolina; Key, Tim; Leitzmann, Michael; Powers, Hilary; Wiseman, Martin; Romieu, Isabelle
Abstract: Lifestyle factors, including diet, have long been recognised as potentially important determinants of cancer risk. In addition to the significant role diet plays in affecting body fatness, a risk factor for several cancers, experimental studies have indicated that diet may influence the cancer process in several ways. Prospective studies have shown that dietary patterns characterised by higher intakes of fruits, vegetables, and whole-grain foods, and lower intakes of red and processed meats and salt, are related to reduced risks of death and cancer, and that a healthy diet can improve overall survival after diagnosis of breast and colorectal cancers. There is evidence that high intakes of fruit and vegetables may reduce the risk of cancers of the aerodigestive tract, and the evidence that dietary fibre protects against colorectal cancer is convincing. Red and processed meats increase the risk of colorectal cancer. Diets rich in high-calorie foods, such as fatty and sugary foods, may lead to increased calorie intake, thereby promoting obesity and leading to an increased risk of cancer. There is some evidence that sugary drinks are related to an increased risk of pancreatic cancer. Taking this evidence into account, the 4th edition of the European Code against Cancer recommends that people have a healthy diet to reduce their risk of cancer: they should eat plenty of whole grains, pulses, vegetables and fruits; limit high-calorie foods (foods high in sugar or fat); avoid sugary drinks and processed meat; and limit red meat and foods high in salt.